Prevalence of work related musculoskeletal disorders among construction workers in Hayatabad Peshawar KP, Pakistan - Attaullah; Sardar Changez Khan; Sana Ullah; Haider Darain; Mujeeb Ur Rahman (Rehman Journal of Health Sciences, 2019)
Introduction: Construction is one the blue-collar jobs where individuals are prone to sustain musculoskeletal injuries. As a result, construction workers are forced in abandoning their work prematurely causing a significant burden on the community. Little is known about the frequency of these injuries in construction workers involved in construction industry of Hayatabad and therefore, this survey was designed.